Pre-service mathematics teachers’ pedagogical content knowledge regarding student mistakes on the subject of circle - Zeki Aksu (International Journal of Evaluation and Research in Education (IJERE), 2019)
The aim of this study is to examine the pre-service teachers' pedagogical content knowledge about the subject of circle in the context of knowing the source of students' mistakes and offering correct solutions. The participants of the study consisted of 30 pre-service teachers who were studying in the last grade of Department of Mathematics Education. In the study, the data were collected through open-ended questions with the qualitative approach. It was determined that the pre-service teachers were not at the desired level in terms of identifying the source of students' mistakes and proposing correct solutions. It is very important for pre-service teachers to be aware of their pedagogical content knowledge levels for their professional careers.